A reappraisal of the role of humans in the biotic disturbance of islands. (12th April 2017) - DELGADO, JUAN D.; RIERA, RODRIGO; RODRÍGUEZ, RICARDO A.; GONZÁLEZ-MORENO, PABLO; FERNÁNDEZ-PALACIOS, JOSÉ MARÍA
SUMMARY: Traditionally, islands have been used as ecological and biogeographical models because of their assumed ecological simplicity, reduced ecosystem size and isolation. The vast number of Earth's oceanic islands play a key role in maintaining global biodiversity and serve as a rich source of evolutionary novelty. Research into the factors determining diversity patterns on islands must disentangle natural phenomena from anthropogenic causes of habitat transformation, interruption and enhancement of biological fluxes and species losses and gains in these geographically and ecologically limited environments. The anthropogenic ecological forcing of communication through global transport has profound implications regarding island–continent links. Anthropogenic disturbances along continental margins and insular coasts contribute to shaping island biotas in ecological time, but also have evolutionary consequences of global resonance. Patterns of human landscape and resource use (geographical space and ecological communities and species), as well as increasing ecological connectivity of oceanic islands and mainland, are chief driving forces in island biogeography that should be reappraised. Global indirect effects of human activities (i.e. climate change) may also affect islands and interact with these processes. We review the implications of direct and indirect anthropogenic disturbances on island biotic patterns, focusing on island size, isolation and introduced exotic species, as well as the unsettled issue of oceanic island ecological vulnerability.